“Hermeneutics For Judges in Deciding Case Number: 66/Pid.Sus/2021/Pn. Brb” - Mahyuni Mahyuni (Green Publisher, 2025)
This thesis research aims to find the basis of Hermeneutics in the Judge's Decision, in case Number 66/Pid.Sus/2021/Pn.Brb, related to the problem of illegal narcotics trade and complex narcotics crimes because there are three factors causing the increase in illegal narcotics circulation, namely weak interdiction capacity which will result in an increase in the risk of illicit narcotics trafficking, increased narcotics abuse which results in increased demand for narcotics, and lack of cooperation between law enforcement agencies both nationally and internationally. This research uses a normative legal research method, namely, which is carried out by examining norms or laws as its source. This research aims to find legal rules, legal principles, or legal doctrines to answer the legal issues faced. The results of this research based on the Judge's decision state that the defendant's actions are considered to violate Article 114 paragraph (1) of Law No. 35/2009 concerning Narcotics, subsidiary Article 112 paragraph (1) of Law of the Republic of Indonesia Number 35 of 2009 concerning narcotics. In criminal cases such as Number 66/Pid.Sus/2021/Pn.Brb, some of the bases underlying the use of hermeneutics in case Number 66/Pid.Sus/2021/Pn.Brb include the complexity of legal facts, limitations of legal texts and plurality of Interpretation: Law is not an exact science. There is the possibility of various interpretations of a legal rule. Hermeneutics encourages judges to make critical and rational interpretations, by considering various points of view.